Behavioural subphenotypes and their anatomic correlates in neurodegenerative disease. Issue 2 (27th February 2023) - Roy, Ashlin R K; Datta, Samir; Hardy, Emily; Sturm, Virginia E; Kramer, Joel H; Seeley, William W; Rankin, Katherine P; Rosen, Howard J; Miller, Bruce L; Perry, David C
Abstract: Patients with neurodegenerative disorders experience a range of neuropsychiatric symptoms. The neural correlates have been explored for many individual symptoms, such as apathy and disinhibition. Atrophy patterns have also been associated with broadly recognized syndromes that bring together multiple symptoms, such as the behavioural variant of frontotemporal dementia. There is substantial heterogeneity of symptoms, with partial overlap of behaviour and affected neuroanatomy across and within dementia subtypes. It is not well established if there are anatomically distinct behavioural subphenotypes in neurodegenerative disease. The objective of this study was to identify shared behavioural profiles in frontotemporal dementia-spectrum and Alzheimer's disease-related syndromes. Additionally, we sought to determine the underlying neural correlates of these symptom clusters. Two hundred and eighty-one patients diagnosed with one of seven different dementia syndromes, in addition to healthy controls and individuals with mild cognitive impairment, completed a 109-item assessment capturing the severity of a range of clinical behaviours. A principal component analysis captured distinct clusters of related behaviours. Voxel-based morphometry analyses were used to identify regions of volume loss associated with each component. Seven components were identified and interpreted as capturing the following behaviours: Component 1—emotional bluntness, 2—emotional lability and disinhibition, 3—neuroticism, 4—rigidity and impatience, 5—indiscriminate consumption, 6—psychosis and 7—Geschwind syndrome-related behaviours. Correlations with structural brain volume revealed distinct neuroanatomical patterns associated with each component, including after controlling for diagnosis, suggesting that localized neurodegeneration can lead to the development of behavioural symptom clusters across various dementia syndromes. Abstract : Patients with one of seven different dementia syndromes, mild cognitive impairment, or controls ( n = 281), completed a 109-item assessment capturing the severity of a range of clinical behaviours. A principal component analysis identified seven components of related behaviours. Imaging analyses identified regions of volume loss associated with each component. Graphical Abstract: Graphical Abstract